Dramatic Curiosity Dengan Pengembangan Produk Sistematis Pada Penceritaan Animasi 2D â€œKaratekaâ€ - Maharani, Faiza Zahwa; Dewi, Nuria Indah Kurnia; Atmani, Agnes Karina Pritha (Jurnal Ilmiah Multimedia dan Komunikasi, 2025)
Performance anxiety is a common type of anxiety experienced by athletes in the realm of sports, even among those in excellent physical condition. This anxiety significantly impacts athletes' mental and psychological performance, which serves as the inspiration for creating a 2D animated film titled Karateka. The film addresses the theme of performance anxiety among athletes. Additionally, animated films that explore anxiety within the context of sports are relatively limited in number. The first step in creating the Karateka 2D animated film was determining the core idea based on the issue to be discussed. This idea was then developed into a script through the process of structuring the storyline. As a result, a compelling narrative and plot were crafted to captivate the audienceâ€™s interest in this 2D animated film. To further engage viewers, the creator incorporated elements of dramatic curiosity into the film. In developing the script for Karateka, the ADDIE method (Analysis, Design, Development, Implementation, and Evaluation) was employed. During the analysis stage, the creator conducted a literature review and observational studies. In the design phase, dramatic curiosity was distributed throughout the storyline using a dramatic graph. The development stage involved refining the plot and story outline, while the implementation phase focused on creating script segments infused with elements of dramatic curiosity. Finally, during the evaluation stage, the creator conducted focus group discussions and expert validation tests to assess the application of curiosity elements in the developed segments